(untitled) (Research, Society and Development, 2023)
The demand for foods that do not have raw materials of animal origin in their formulation is constantly growing. The reason for this is the number of people who call themselves vegetarians or vegans, who have health problems or who opt for restrictive diets for various reasons. Problems related to milk consumption, such as protein allergy and lactose intolerance, affect a large part of the population, and it is necessary to develop products that meet the needs of these consumers. With a view to the development of products analogous to cow’s milk, several studies are being carried out on plant extracts. This study aimed to evaluate consumer expectations about the production of vegan ice cream based on water-soluble cashew nut extract, in order to prove its acceptance for possible production viability. The consumption expectation analysis was carried out using an electronic form with a structured questionnaire, presenting two formulations to the participants, with different concentrations of the water-soluble extract, with sample A using extract in the proportion of 1:3 and sample B the proportion of 1:5. It was possible to obtain favorable results, with an acceptance rate for sample A of 91.90% and for sample B of 76.20%. In this way, the visual acceptability of the ice cream produced with cashew nut extract highlights its potential in replacing dairy derivatives, providing an alternative for people who need or want to give up animal milk, whether for health reasons or by choice.